Nonparametric statistical study for the crime motives on a sample of inmates in Khartoum State prisons - محمد بدوي عثمان (Journal of Economics and Administrative Sciences, 2017)
The aim of the research was to investigate the use of non-parametric tests in the analysis of the questionnaire and how to choose the appropriate test for testing the hypothesis of the study of crime motives in Khartoum State. The data were collected through the primary sources by designing a questionnaire and distributed to a sample of inmates in Khartoum state; the data were analysis by SPSS program using the analytical statistical method through using some of the suitable non-parametric tests for each case. The most important results of the research were: there was significant relationship between the type of crime and the age group therefore, we found that the age group (20-29) was the most frequent crime particularly, the financial crime. The existence of a statistical relationship between the type of crime and the education level, we found that the illiterate are the most frequent crime of drunk and drugs, the existence of a statistical relationship between the type of crime and the social situation, where we find that the married was the most frequent crime, especially vulnerable. Also the results of the study revealed that there were significant differences for each of the economic, psychological and social factors for committing the crime due to gender, whereas females were the most affected by these factors. Finally there were significant differences in the crime motives due to the (economic, psychological and social factor), so there were significant differences between the economic factor and the psychological factor in favor of the psychological, and between the social factor and the psychological factor in favor of the psychological.